PENGEMBANGAN METODA ANALISA KIMIA UNTUK PEMANTAUAN PROSES FERMENTASI PEMBUATAN ASAM CUKA, ANTIBIOTIKA DAN HORMON STEROID - A. T. Karossi; Julia Kantasubrata (Research Center for Chemistry - LIPI, 1991)
Chemical analysis plays an important role in monitoring fermentationprocess and determining product quality of the process. Nowadays the development of analytical methods, which commenced from relatively conventional method to instrumental method, has become a reality. The development does not only increase either sensitivity or reproducibility, but also could identify the existence of substances produced during fermentation, which could not be achieved by conventional methods. In this article, several chemical analyses used for monitoring the production of vinegar, antibiotic and steroid harmon are described. In vinegar fermentation, analyses cover the determination of sllgars, ethanol and organic acids, while in antibiotic fermentation, in addition to determination of sugar, analyses of tetracycline derivatives as fermentation products, is also carried out. In steroid fermentation, analysis covers the determination of solasodine as substrate, AD and ADD as fermentation products.